Economic effects of mobile technologies on operations of sales agents - Grigori Pichtchoulov; Knut Richter (European University Viadrina, Department of Business Administration and Economics, 2005)
In the presented paper we introduce an approach to assess particular economic effects which may arise with bringing mobile technologies into the field of sales and distribution. The research problem posed here comprises quite a special case where sales operations of a company are carried by its sales representatives, which may count as a resource allocation problem. We apply stochastic programming methodology to model the agent's multistage decision making in a distribution system with uncertain customer demands, and exemplify a potential improvement in the company's overall performance when mobile facilities are utilized for making decisions. We provide finally an efficient computational algorithm that delivers optimal decision making with and without mobile technologies, and computers the expected overall performance in both cases, for any configuration of a distribution system. Some computational results are presented.
Keywords: 330; Handelsvertretung; Mehrstufige Entscheidung; Vertrieb; Mobilkommunikation; Mathematische Optimierung; Stochastischer Prozess; Theorie